2016
DOI: 10.1186/s40561-016-0029-z
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of enhanced educational experiences using interactive videos and web technologies: pedagogical and architectural considerations

Abstract: Nowadays, teachers and students utilize different ICT devices for conducting innovative and educational activities from anywhere at any time. The enactment of these activities relies on robust communication and computational infrastructures used for supporting technological devices enabling better accessibility to educational resources and pedagogical scaffolds, wherever and whenever necessary. In this paper, we present EDU.Tube: an interactive environment that relies on web and mobile solutions offered to tea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 28 publications
0
11
0
1
Order By: Relevance
“…For example, smartphones are used as clickers to complete questionnaires and assignments [26], [38]- [41]. Alternatively, smartphones are used to visualize learning contents [32], [42], [43].…”
Section: Characterization Of Slesmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, smartphones are used as clickers to complete questionnaires and assignments [26], [38]- [41]. Alternatively, smartphones are used to visualize learning contents [32], [42], [43].…”
Section: Characterization Of Slesmentioning
confidence: 99%
“…Learning management systems (LMSs) were referenced in [28], [29], [35], [38], [39], [42]- [46], [49], [50], [53], [58], [59], [62], [63], [87], [88] Desktop computers 17 (25%) [19], [21], [22], [24], [31], [33], [40], [42], [43], [60], [63], [64], [67], [73], [77], [78], [87] Learning management system 14 (20.59%)…”
Section: B Technologies Involved In Slesmentioning
confidence: 99%
See 1 more Smart Citation
“…Ahora bien, ¿cuál es la diferencia entre las seis categorías que tienen este común denominador?, la diferencia radica en qué principios consideran y cómo los emplean en su proceso de desarrollo, puesto que se puede considerar, desde un aspecto muy general, como un elemento en el proceso de desarrollo (Coomans & Lacerda, 2015;Golitsyna, 2015), o como una fuente de conceptos técnicos, necesarios para describir la estructura de la plataforma de tecnología educativa en su totalidad mediante patrones de diseño y patrones arquitectónicos, siendo ambos conceptos medulares de la Ingeniería de Software (Aguña, 2012;Campo et al, 2020;Chimalakonda & Nori, 2018;Devedžić & Jovanović, 2015;Kohen-Vacs et al, 2016;Marcolino & Barbosa, 2017;Pástor et al, 2018;Sengupta et al, 2009;Sengupta & Dasgupta, 2017a, 2017b.…”
Section: Aplicación De Los Principios De Ingeniería De Softwareunclassified
“…Despite the evidence that the authors provided on the effectiveness of interactive videos when compared to linear non-interactive versions, interactive videos were not really adopted in educational settings or research efforts in the years to follow. It was until recently and most likely due to the technological evolution of web video players that interactive videos enriched with in-video quizzes made their appearance again and have been the focus in a number of research studies (Cummins, et al, 2015;Wachtler et al, 2016;Kohen et al, 2016). Cummins et al research results demonstrated that in-video quizzes were successful in creating an engaging and interactive mode of content delivery.…”
Section: Interactive Videosmentioning
confidence: 99%